2022
DOI: 10.1002/adfm.202211821
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Multistage Coupling of FeS2/S Enables Ultrahigh Reversible Na–S Batteries

Abstract: The fundamental challenges that coexisted around sulfur cathode energy storage systems, are the severe polysulfide dissolution and low reactivity resulting in poor reversibility and short cycle life, specifically, in inexpensive sodium ion batteries. Herein, the solution‐processed synthesis of ultra‐high intimate contacted FeS2/S architecture is reported and evolution of the dynamic multistage coupling between the FeS2 and S in sodium–sulfur batteries is revealed. Atomic visualization and in situ spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…Different from the surface gelation of MoS 2 , a reversible phase transformation of metal sulfide FeS 2 to Na x FeS 2 (0 < x ≤1) was observed by Chen et al in Na-S batteries. [189] The results of in situ Raman spectra indicated that the ultrahigh intimate contacted FeS 2 /S architecture prompted the reversible formation and decomposition of Na 2 S 2 /Na 2 S (Figure 10f,g). By contrast, with the commercial FeS 2 substrate, only Na 2 S 4 was [183] Copyright 2021, Wiley-VCH.…”
Section: Metal Sulfidesmentioning
confidence: 98%
“…Different from the surface gelation of MoS 2 , a reversible phase transformation of metal sulfide FeS 2 to Na x FeS 2 (0 < x ≤1) was observed by Chen et al in Na-S batteries. [189] The results of in situ Raman spectra indicated that the ultrahigh intimate contacted FeS 2 /S architecture prompted the reversible formation and decomposition of Na 2 S 2 /Na 2 S (Figure 10f,g). By contrast, with the commercial FeS 2 substrate, only Na 2 S 4 was [183] Copyright 2021, Wiley-VCH.…”
Section: Metal Sulfidesmentioning
confidence: 98%
“…[1,2] The key electrode materials have been fully explored in the past few years and are being used in the process of industrialization, including important cathodes (transition metal oxides (TMOs), polyanionic compounds, and Prussian blue analogues (PBAs)) [3] and hard carbon (HC) anode. [4,5] However, HC suffers the low initial Coulombic efficiency (ICE), poor cycle stability, and rate performance in typical organic electrolytes [6] given that the formed solid electrolyte interphase (SEI) on the defect-rich HC is uneven, thick, and easy to break because of its poor mechanical strength. The resulting excessive consumption of electrolytes and increasing interface impedance reduce its ICE, cycle stability, and reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the aforementioned shortcomings, extensive research has been conducted on the design and assembly technology of composite sulfur cathode with high mechanical stability and long‐cycling reliability. This includes the kinetics of the sulfur cathode, [ 4 ] doping of elements carbon or nitrogen, in suit coating with inorganic or organic materials on sulfur or adding an interlayer between the cathode and separator. [ 2b,5 ] Surface coating technology, as a common electrode treatment method, has the remarkable advantages such as strong universality, controllable processing cost, and easy process implementation.…”
Section: Introductionmentioning
confidence: 99%